Aloe vera Coatings Help Extend Shelf Life and Maintain Nutritional Quality of Ber Fruit - Taslima Ayesha Aktar Nasrin; Rafiq Islam; Mafruha Afroz; Md. Atiqur Rahman; Most. Sadia Arfin; Mohammad Mainuddin Molla; Ashfak Ahmed Sabuz (Applied Fruit Science, 2026)

Climate-smart management of rice–pulse rotations in complex coastal saline ecosystems: an APSIM assessment - Sukamal Sarkar; Donald S. Gaydon; Mohammad Kamruzzaman; Mohammed Mainuddin; Anannya Dhar; Saikat Dey; Koushik Brahmachari (Agricultural Systems, 2025)

Advancements in Extreme Precipitation Projections for South Asia: A Comparative Evaluation of CMIP5 and CMIP6 Models - Mohammad Kamruzzaman; Shahriar Wahid; Mohammed Mainuddin; Francis Chiew; Abu Reza Md Towfiqul Islam; Mohammed Magdy Hamed; Kelly R. Thorp; Shamsuddin Shahid (International Journal of Climatology, 2025)
Global climate models (GCMs) are essential for projecting future climate changes, yet their ability to accurately simulate extreme precipitation, particularly in South Asia, remains a major challenge. This study assessed the performance of GCMs from CMIP5 and CMIP6 in replicating 11 extreme precipitation indices, using ERA5 data from 1975 to 2005. The results revealed substantial variability across individual models, with CMIP6 generally outperforming CMIP5, though certain inconsistencies persisted. Both CMIP5 and CMIP6 multi‐model ensemble means (MMEs) exhibited higher root mean square error (RMSE) than the best individual models, highlighting the need for further improvements in model accuracy. On average, CMIP6 models achieved a Kling–Gupta efficiency (KGE) of 0.42, outperforming CMIP5's 0.38, and demonstrated better agreement in Taylor diagrams, with an average r 2 of 0.65 compared to 0.59 for CMIP5. CMIP6 also showed reduced uncertainty in interannual monthly precipitation variability projections. EC‐Earth3 (CMIP6) and EC‐Earth (CMIP5) consistently correlated well with various indices, while MIROC‐ESM was also a strong performer in both generations. The CMIP6 MME performed better overall, with a KGE of 0.48 and r 2 of 0.71, surpassing CMIP5 MME's 0.44 and 0.67. Future projections indicate significant changes in precipitation extremes under different emission scenarios for the 2040s and 2080s. While CMIP6 shows clear advancements over CMIP5, continued model refinement is essential to more accurately simulate extreme precipitation events.

Mapping the landscape of APSIM-driven agricultural research: a bibliometric analysis and future perspectives - Sukamal Sarkar; Saikat Dey; Anannya Dhar; Apurbo K. Chaki; Rupak Goswami; Donald S. Gaydon; Sourav Garai; Koushik Brahmachari; Mohammad Mainuddin (International Journal of Biometeorology, 2025)

Strategies of water resource utilization and agricultural water management in the coastal saline zone of Bangladesh - Md. Belal Hossain; Debjit Roy; Priya Lal Chandra Paul; Mst. Shetara Yesmin; Palash Kumar Kundu; Mohammad Rezoan Bin Hafiz Pranto; Md Aklimuzzaman; Mousumi Paul; Md. Maniruzzaman; Mohammed Mainuddin (Irrigation and Drainage, 2025)
Access to irrigation water is pivotal for dry season crops in the coastal saline regions of Bangladesh. This research investigates strategic measures aimed at ensuring water availability for polder agricultural purposes in the dry season. This study was performed from 2017 to 2022 to assess the water availability inside polders # 30 and # 31 in Khulna region of the south‐western coastal zone of Bangladesh. Our methodology encompassed diverse approaches: identifying optimal water sources, capturing low‐salinity water for agriculture, implementing crop–soil–water management to enhance cropping intensity, employing irrigation modelling for effective crop planning, utilizing GIS techniques to estimate water storage and conducting impact analysis using satellite images. Irrigation by trapped river water increased the yield of different crops by 13–56% compared with that of farmer‐managed plots. Polders # 30 and # 31 currently have approximately 136 and 190 km of good canals, which store 334 and 502 ha‐m of water, respectively, during the dry period. With the existing stored fresh water, a maximum of 6,680 ha and 10,040 ha of watermelon and a minimum of 334 and 502 ha of boro rice cultivation were possible in polders # 30 and # 31, respectively. However, the excavation of poor and dead canals could increase freshwater storage and crop coverage. The image analysis of polder #31 revealed an increase in crop coverage of 238% from 2017 to 2022, which might be attributed to the introduction of advanced water management technologies and salt‐tolerant cultivars as well as holistic extension approaches by different government organizations (GOs), non‐governmental organizations (NGOs) and farmers. This study will assist in formulating pathways for polder‐scale water management and cropping intensification in coastal saline zones.

Impact of green space and built environment on metabolic syndrome: A systematic review with meta-analysis - Muhammad Mainuddin Patwary; Mohammad Javad Zare Sakhvidi; Sadia Ashraf; Payam Dadvand; Matthew H.E.M. Browning; Md Ashraful Alam; Michelle L. Bell; Peter James; Thomas Astell-Burt (Science of The Total Environment, 2024)

Evaluation of green chili stored at the chilling condition: Effects of thermal and ultrasound pretreatments - Mahfujul Alam; Mrityunjoy Biswas; Mrinal Kanti Debnath; Mir Meahadi Hasan; Md. Rakibul Islam; Avishek Jodder; Asraful Alam; Md. Ashrafuzzaman Zahid; Md. Abdul Alim; Md. Arif Chowdhury; Chanchal Molla; Mohammad Mainuddin Molla (Food and Humanity, 2023)

Storm protection service of the Sundarbans mangrove forest, Bangladesh - Md. Ali Akber; Muhammad Mainuddin Patwary; Md. Atikul Islam; Mohammad Rezaur Rahman (Natural Hazards, 2018)